P112 Studying cellular senescence in human lymph node stromal cells during the earliest phases of rheumatoid arthritis - De Jong, TA; Timmerman, AL; Semmelink, JF; Hähnlein, JS; van Baarsen, LG (Annals of the rheumatic diseases, 2019)
Career situation of first and presenting authorStudent for a master or a PhD.IntroductionCellular senescence is a state of proliferation arrest of cells. The persistence and accumulation of senescent cells has been implicated in the pathogenesis of age-related diseases. Ageing is an important risk factor of rheumatoid arthritis (RA), a prototypic autoimmune disease in which loss of immune tolerance and systemic autoimmunity precedes clinical onset of disease. Through their intimate contact with lymphocytes, lymph node stromal cells (LNSCs) are important regulators of peripheral tolerance. Therefore, malfunctioning senescent LNSCs may potentially lead to defective peripheral tolerance and the development of systemic autoimmune disease.ObjectivesTo determine the extent of cellular senescence of LNSCs during early phases of systemic autoimmunity.MethodsWe included individuals with arthralgia without any evidence of arthritis who were positive for IgM rheumatoid factor (IgM-RF) and/or anti-citrullinated protein antibodies (ACPA; RA-risk group), early arthritis patients (ACR/EULAR 2010 criteria; disease duration <1 year) and seronegative healthy controls. All study subjects underwent ultrasound-guided inguinal lymph node biopsy. LNSCs were cultured from freshly collected lymph node needle biopsies and passages 0–9 were used for experiments. Flow cytometry, qPCR and microscopy were used to measure cell size, granularity, senescence-associated gene expression levels, telomere attrition and senescence-associated β-galactosidase (SA β-gal) activity.ResultsPreliminary flow cytometry data shows that the cell size of LNSCs from RA patients (n=11) and RA-risk individuals (n=7) is increased compared with healthy LNSCs (n=7), while granularity was specifically increased in LNSCs from RA patients (n=9). Initial SA β-gal stainings indicate higher activity in LNSCs from RA-risk (n=3) and RA patients (n=4) compared with healthy controls (n=2), however this data needs to be carefully interpreted and more donors should be analysed. Expression levels of senescence-associated genes significantly increased over culture passages and significantly higher p21 and p53 levels were observed in passage 9 LNSCs from RA patients compared with healthy controls (n=6 per group).ConclusionsThese preliminary findings provide a rationale for studying cellular senescence in LNSCs in more detail during different phases of RA and to investigate the consequence of senescent LNSCs on immune cell responses upon their interaction.Disclosure of InterestNone declared.